Antibacterial Activity of 96% Ethanol Extract from Red Rice Bran (Oryza nivara) Against Escherichia coli: Uji Aktivitas Antibakteri Ekstrak Etanol 96% Bekatul Beras Merah (Oryza nivara) terhadap Escherichia coli - Ni Luh Gde Mona Monika; Ni Wayan Rika Kumara Dewi; Ni Putu Gita Puspita Sari (Institut Teknologi dan Kesehatan Bintang Persada, 2023)
Red rice bran is a by-product produced from rice milling in Jatiluwih village, Tabanan, Bali which has secondary metabolites that have the potential to inhibit bacterial activity. The purpose of this study was to determine the potential of 96% ethanol extract of red rice bran to inhibit bacterial growth Escherichia coli. The research method started with the extraction process by maceration method using 96% ethanol solvent. The viscous extract obtained was then subjected to phytochemical screening which showed the presence of compounds flavonoid, alkaloid, and tannin. Antibacterial activity test using disc diffusion method paper disk, measured by looking at the clear zone formed and analyzed using the mean test. The antibacterial activity test results of red rice bran extract at concentrations of 20% (8.63 mm) and 25% (9.93 mm) were categorized as moderate, concentration 30% (10.33 mm) was categorized as strong inhibition. Positive control in this study using chloramphenicol 250 mg which resulted in an inhibition zone of 21.42 mm in the strong inhibition zone category. Comparison of the antibacterial activity of the 96% ethanol extract of red rice bran showed significant difference with p value <0.05.